2010
DOI: 10.1111/j.1442-2050.2010.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of risk factors obesity and occupational airborne exposures with CDKN2A/p16 aberrant DNA methylation in esophageal cancer patients

Abstract: It is known that obesity and occupational airborne exposure such as dust are among risk factors of esophageal cancer development, in particular squamous cell carcinoma (SCC) of esophagus. Here, we tested whether these factors could also affect aberrant DNA methylation. DNAs from 44 fresh tumor tissues and 19 non-tumor adjacent normal tissues, obtained from 44 patients affected by SCC of esophagus (SCCE), were studied for methylation at the CDKN2A/p16 gene promoter by methylation-specific polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…To our knowledge, there are few studies that have explored the relation between aberrant DNA methylation and overweight and obesity in human cancers of any site (24,(40)(41)(42)(43). In normal autopsy kidney tissues, it was reported that the promoter methylation of the RASSF1A gene was significantly increased in the obese group (BMI 30) than in the normal-weight group (BMI of 20 -25) (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there are few studies that have explored the relation between aberrant DNA methylation and overweight and obesity in human cancers of any site (24,(40)(41)(42)(43). In normal autopsy kidney tissues, it was reported that the promoter methylation of the RASSF1A gene was significantly increased in the obese group (BMI 30) than in the normal-weight group (BMI of 20 -25) (41).…”
Section: Discussionmentioning
confidence: 99%
“…Although we chose to examine 3 genes that have been identified as frequently methylated in breast tumors, other genes, including RASSF1A (41), may be more informative for examination, specifically with regard to differences by BMI or body weight. As was the case in other studies (24,42,43), the qualitative nature of the real-time methylation-specific PCR method limited our ability to detect quantitative changes in the methylation of genes. Furthermore, our inability to obtain archived tumor tissue for all breast cancer cases may have led to a selection bias.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Iran is located in the so-called Asian esophageal cancer belt where reports indicate the highest incidence rate of squamous cell carcinoma of esophagus (SCCE) of the world from certain parts of this country. Although recent reports [40][41][42][43] indicate attempts for identifying the molecular etiology of SCCE in addition to achievement of suitable tumor markers for this cancer, such efforts have so far been unconvincing and further efforts are therefore required [34]. Delayed diagnosis is a major problem associated with SCCE that most often results in diagnosis of the disease in the advanced stages of tumorigenesis.…”
Section: Aat and Esophageal Cancermentioning
confidence: 99%
“…Inactivation of p16/INK4a is a common event in esophageal cancer and occurs through homozygous deletion, point mutation and/or hypermethylation [181][182][183][184]. In SCCE, homozygous deletion and promoter methylation are the major causes of p16/INK4a gene silencing, while somatic mutation is a rare event [185].…”
Section: P16/ink4a and P15/ink4bmentioning
confidence: 99%